KEPANIKAN MORAL DAN DAKWAH ISLAM POPULER (Membaca Fenomena ‘Rohis’ di Indonesia) - Kailani, Najib (Universitas Islam Negeri Raden Intan Lampung, 2011)
The phenomenon of Islamic spirituality in campus turns out to not only be a political and preaching movement, but is also related to “moral panic” that overwhelms the Indonesian society, especially after a massive penetration of Western and East Asian pop culture. This article is the result of an intensive research involving a number of Senior High Schools students in Yogyakarta in 2008-2009. It was found that the flood of pop culture since the 1970s have produced a counter reaction i.e. pop as a counter culture to the Islamic circle. Worries about the “ghost” of pop culture among adolescent are shown in a guidance book of Islamic preaching in school. Such moral panic recently caused the proselytizing movement in school or popularly called ‘Rohis’ to become more popular among Indonesian Moslem adolescent.